Strategy of Mandibular Central Arch Reconstruction after Firearm Injury - Fernandes, Breno Dos Reis [UNESP]; Mendes, Bruno Coelho [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Okamoto, Roberta [UNESP]; Homsi, Nicolas; Rocha, Hernando Valentim Da; Magacho, Luiz Fernando; Pereira, Rodrigo Dos Santos [UNESP] (Wolters Kluwer, 2019)
Gunshot wounds can cause extensive destruction of soft tissue and bone, and the maxillofacial region is often affected. The reconstructive treatment is complex due to the difficulty to reestablish the central arch mandibular contour and volume. Moreover, the goal is to avoid postoperative infections and obtain bone graft neovascularization. Therefore, this report shows a clinical case of a patient presenting mandibular deformity with a mandibular central arch discontinuity caused by a firearm injury. The strategy to the reconstructive treatment as performed with a condensed and stabilized particulate autogenous bone graft was essential and effectiveness. After 1 year, it was obtained a satisfactory result to the patient.
Keywords: Gunshot; head trauma; maxillofacial injuries; wounds